Peran Pemeriksaan Penanda Tumor Cairan Pleura dalam Diagnosis Efusi Pleura Maligna Akibat Kanker Paru Primer - Rumende, Cleopas M; Sutandyo, Noorwati; Hanafi, Arif R; Rumende, Samuel K; Susanto, Erwin C; Sitorus, Truely P (Jurnal Penyakit Dalam Indonesia, 2024)
Introduction. Pleural effusion is a frequently acquired lung disorder and based on the type of cause it is divided into malignant and non-malignant pleural effusion. Cytological examination of pleural fluid to differentiate between malignant and non-malignant pleural effusion shows varying sensitivity. Research regarding the benefits of CEA and Cyfra 21-1 pleural fluid examination to detect malignant pleural effusion due to primary lung cancer in Indonesia is still very limited. The aims of this study is to determine the sensitivity and specificity of CEA and Cyfra 21-1 pleural fluid in diagnosing malignant pleural effusion due to primary lung camcer. Methods. A cross-sectional diagnostic study was conducted on patients with exudative pleural effusion at Dr. Cipto Mangunkusumo National Hospital (RSCM) and Darmais Cancer Hospital between September 2015 and May 2016. Patients underwent examinations for carcinoembryonic antigen (CEA) and cytokeratin 19 fragment (Cyfra 21-1) in their pleural fluid. The ROC curves were generated to determine the optimal cut-off values for CEA and Cyfra 21-1 concentrations in pleural effusion, considering the area under the curve (AUC) obtained. Chi-square tests were performed to assess sensitivity and specificity, as well as to calculate positive predictive value, negative predictive value, and accuracy for each cut-off value for both CEA and Cyfra 21-1. Results. A total of 122 patients with exudative pleural effusion, positive cytology results were obtained in 80 patients. By using the CEA cut-off value of 4.23 ng/ml, the sensitivity, specificity, positive predictive value, negative predictive value and accuracy were 87.50%, 80.95%, 89.74%, 77.27% and 85.25% with an AUC value of 0.878 (0.814 - 0.942). By using the Cyfra 21-1 cut-off value of 26.9 ng/ml, the sensitivity, specificity, positive predictive value, negative predictive value and accuracy were 78.75%, 71.43%, 84.00%, 63.82% and 76.23% with an AUC value of 0.817 (0.739 - 0.896). Conclusion. Examination of CEA and Cyfra 21-1 level in pleural fluid can be used to support the diagnose of malignant pleural effusion due to primary lung cancer.